As "Bonecas" da pista no horizonte da cidadania: uma jornada no cotidiano travesti em Belém (PA) - FERREIRA, Rubens da Silva (Universidade Federal do Pará, 2012)
The present work is a study on the travestytis that live of prostitution in the streets of Belem, state of Para, Brazil. The venal activity that guarantees the sustenance to them admittedly is practiced in the avenues Almirante Barroso and Assis de Vasconcelos, located respectively in the Marco and the Campina’s boroughs. These public ways function as two important corridors of traffic of vehicles of the city, being therefore ideal to trottoir them. The empirical data collected through interviews and field notes had served to the intention of knowing the reality where these professionals of the sex live, which consolidates as hypothesis the idea that their androgynous appearance turns them citizens socio-devaluated with direct implications in their citizenship. It is revealing in this direction, the lack of public politics to this social segment in a way that they fit in the homosexuality concept, especially while a more generic category to explain the desire and the love among people of the same sex. Both in national and local levels, it is possible to verify attempts of implementation of public politics in the form of antidiscriminatory laws that aim not only to benefit gays, but also to the lesbians and travestytis, however these social categoris have been target of resistances of contrary parliamentarians to the advance of the citizenship of these citizens. Among others things, it was evidenced in this direction that the construction of the citizenship for the travestytis in the city is dependent of the performance of the Homosexual Movement of Belem (HMB) in the political mobilization towards rights, as they are not organized such as occurs in other Brazilian capitals. Therefore, one understands that there is a lot to advance regarding social and civil guarantees, so these androgynous citizens, popularly known as "dolls", in fact and through right can become citizens.